(untitled) (University Journal of Zoology, Rajshahi University, 2013)
To study the big and Small Indigenous Species (SIS) of fish production, 15 ponds of Rajshahi University campus were selected. The pond production was ranged from 326.16 to 2187.40 kg/ha. The ratio of SIS and big fish production was calculated maximum as 1 : 0.10 (by number) and 1 : 7.46 (by weight). Majority of these SIS fish are Self Recruiting Species (SRS), because they were not stocked in the studied ponds. The F/C ratio was obtained as 4.583 in average DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15378 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 27-30